Technical Advance: Transcription factor, promoter, and enhancer utilization in human myeloid cells. Issue 5 (25th February 2015) - Joshi, Anagha; Pooley, Christopher; Freeman, Tom C; Lennartsson, Andreas; Babina, Magda; Schmidl, Christian; Geijtenbeek, Teunis; Michoel, Tom; Severin, Jessica; Itoh, Masayoshi; Lassmann, Timo; Kawaji, Hideya; et al.
Abstract : Analysis of the myeloid transcriptome by integrating 91 samples from the myeloid lineage and AML cell lines to predict novel regulatory interactions, enhancers, miRNAs, and lincRNAs. Abstract: The generation of myeloid cells from their progenitors is regulated at the level of transcription by combinatorial control of key transcription factors influencing cell-fate choice. To unravel the global dynamics of this process at the transcript level, we generated transcription profiles for 91 human cell types of myeloid origin by use of CAGE profiling. The CAGE sequencing of these samples has allowed us to investigate diverse aspects of transcription control during myelopoiesis, such as identification of novel transcription factors, miRNAs, and noncoding RNAs specific to the myeloid lineage. We further reconstructed a transcription regulatory network by clustering coexpressed transcripts and associating them with enriched cis-regulatory motifs. With the use of the bidirectional expression as a proxy for enhancers, we predicted over 2000 novel enhancers, including an enhancer 38 kb downstream of IRF8 and an intronic enhancer in the KIT gene locus. Finally, we highlighted relevance of these data to dissect transcription dynamics during progressive maturation of granulocyte precursors. A multifaceted analysis of the myeloid transcriptome is made available (http://www.myeloidome.roslin.ed.ac.uk ). This high-quality dataset provides a powerful resource to study transcriptional regulation during myelopoiesis and to infer the likely functions of unannotated genes in human innate immunity.